Exploring the Development and the Future Trends of Fintech and E-commerce - Ao, Shih-Yun (2019)
The techniques of fintech and e-commerce have become developed and make a big difference in our lifestyle and quality of life. In addition to introducing the basic concepts of fintech and e-commerce, I also mention the impact of fintech on the entire market and e-commerce, the future development of fintech and e-commerce, and use the examples of different countries and companies to illustrate this topic. I really hope that this dissertation can lay the foundation for people who feel interested in this topic but do not have professional knowledge, and they can also think of some strategies to deal with the changes caused by the development of fintech.